Point of Care with Micro Fluidic Paper Based Device Incorporated with Nanocrys of Zeolite –GO for Electrochemical Sensing of Date Rape Drug. (2017) - Narang, Jagriti; Malhotra, Nitesh; Singhal, Chaitali; Mathur, Ashish; Chakraborty, Dhritiman; Ingle, Aviraj; Pundir, C.S.
Abstract: The objective of the present invention is to develop an ultrasensitive technique for the electro analysis of rape drug. A paper chip (EμPADs) was developed using nanocrystals (Nanocrys) of graphene-oxide and zeolites (Zeo-GO). Nanocrys modified EμPAD showed wide linear range 0.001 - 5 nM/ml and low detection limit of 0.00002 nM/ml. The developed sensor was tested in real time samples like alcoholic and non-alcoholic drinks and found good correlation (99%). Extensive development can be made for industrial translation of this fabricated device.